Serum Magnesium Level among Acute Myocardial Infarction Patients and Its Correlation with Intra-hospital Complications: A Cross-sectional Single-center Study among Sudanese Patients - Mohammed Taha; Ayman Azhary; Nooh Mohamed Hajhamed; Waleed Azhary Sir Alkhatim; Salahdeen Ismail Mohammed; Abdullah M Bakheit; Abdallah Elssir Ahmed; Abubakar Abdelbagi (Sudan Journal of Medical Sciences)
Background: Patients with acute myocardial infarction (AMI) frequently have hypomagnesemia, although magnesium (Mg) has proven cardioprotective characteristics. Cardiovascular fatality has been linked to low serum Mg levels; however, the exact mechanism is unknown and results are inconsistent. This study aims to measure the level of serum Mg among patients diagnosed with AMI. Methods: One hundred AMI patients who came to the Wad Madani Heart Center were included in a cross-sectional research study. Demographic data, clinical data (presenting compliance, medical history, and medication history), laboratory examination, electrocardiography (ECG) findings, and echocardiography findings were collected. Serum Mg was measured for all participants, and hypomagnesemia was considered as a serum Mg level <1.6 mg/dl. Version 21.0 of SPSS was used to analyze the data. Results: The mean age of 100 patients was 60 ± 2 years, with 55 (or 55%) being female and 45 (or 45%) being male. Chest pain (n = 92; 92%) was the major presenting complaint. Moreover, the most prevalent heart disease determinants among patients were diabetes mellitus (n = 50; 50%) and hypertension (n = 50; 50%). The mean of Mg was 2.5 mg/dl, and hypomagnesemia was found in 10 (10%) patients and significantly associated with arrhythmia, namely supraventricular tachycardia, (P-value = 0.01). Patients with normal or low Mg levels (98%) were more likely to be discharged in stable condition, whereas all fatalities were among patients with elevated Mg levels (2%). Conclusion: The frequency of hypomagnesemia among AMI patients was 10%. In addition, hypomagnesemia was significantly associated with arrhythmias (mainly supraventricular tachycardia).